Screening Aspiration Through Hearing in Handling Covid-19 Pandemic of DPRD Blitar Regency - Sheila Vanandea Putri Abadi; Asep Nurjaman (Universitas Teuku Umar, 2022)
Hearing is a significant point that should be practiced by the Regional Government and DPRD through involving the community in gathering information in the field. The purpose of this study was to determine the effectiveness of efforts to acquire aspirations in the DPRD Blitar Regency. The method used in this research is descriptive qualitative. Data collection techniques were interviews, observation, and documentation. The results showed that the Blitar Regency DPRD was very proactive ro acquire aspirations in handling COVID-19 pandemic of Blitar Regency. Further, through hearings, the aspiration screening is more effective. This shows that hearing is very important for the DPRD to absorb people’s aspirations in handling COVID-19 in Blitar Regency. In t1his regard, the DPRD needs to increase its role and function as people’s representatives. Likewise, the Regional Government must be responsive to various community inputs so that COVID-19 pandemic in Blitar Regency can be handled properly.